Aspirational Differences Between Students With and Without IEPs: Grades Earned Matter. (February 2020) - Sinclair, James; Poteat, V. Paul
Using data from the 2015 Dane County Youth Assessment ( n = 12, 886 students, 22 high schools), we identified disparities between students with Individualized Education Programs (IEP) and without IEPs across multiple post–high school aspirations. We identified significant IEP status × grades earned interactions in predicting students' reported likelihood of pursuing post–high school placements. Higher reported average grades earned were more strongly associated with students' greater reported likelihood of attending college/university for students without IEPs than for students with IEPs. Also, higher grades were associated with less likelihood of foregoing postsecondary education and only looking for a job for students without IEPs whereas this association was not significant for students with IEPs. Implications for research and practice are discussed.